Prosedur Pemberian Pembiayaan Pada PT BPR KARANGWARU PRATAMA - Fabhi Nur Laksana; Nugraeni Nugraeni (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
In Indonesia, Law no. 07 of 1992 concerning Banking stipulates two categories of banks: Commercial Banks and Rural Banks. The number of BPRs in Indonesia, according to the Indonesian Banking Statistics Report, totaled 1,552 as of November 2019. Historically, BPRs have existed since the colonial era and have been in contact with small and rural communities. In light of this, the government's policy regarding the establishment of BPRs was facilitated through Pakto 88 and Presidential Decree No. 38 of 1988, which aimed to improve public services. BPRs are currently facing many challenges from the rapidly changing external environment of the industry, including government policies, macroeconomic conditions, competition, and advances in fintech. The purpose of this paper is to analyze the challenges faced by BPR KWP in providing loans and their roles and development efforts, so that BPR KWP continues to develop and play a role in supporting the real sector, especially MSMEs. On the other hand, the changes referred to have indirectly reduced the profitability performance of BPRs over the last five years